Ethics and the Internet in West Africa : toward an ethical model of integration - Brunet, Patrick J., 1952- (Africa World Press ; International Development Research Centre, 2004)
The research behind this book, carried out by means of field surveys, focuses on five nations in West Africa: two Anglophone - The Gambia and Ghana - and three Francophone - Burkina Faso, Côte d'Ivoire, and Senegal. For each country, a portrait of Internet users' ethical behaviours was successfully created. The book demonstrates how the Internet, by virtue of its content and how the technology is uses, is creating upheaval in the practices and modes of communication within African communities. The book culminates with a proposed ethical model for the assimilation of the Internet that could serve as a reference for development policies in each of the respective countries and, more broadly, throughout Africa.